Assessing the Accuracy of SWOT Measurements of Water Bodies in Australia - Louise Maubant; Lachlan Dodd; Paul Tregoning (Geophysical Research Letters)
Abstract The Surface Water and Ocean Topography (SWOT) mission provides an unparalleled observation system for monitoring global surface water resources. We compared different SWOT level‐2 high‐rate products and in situ data for rivers, lakes and reservoirs in Australia, utilizing quality flags and uncertainty indicators present in these data products. Water heights derived from the Raster product have a weighted root‐mean‐square error of ∼5 cm but the product fails to sample small water bodies. The use of LakeSP and RiverSP spatial definitions of water bodies yields accuracies typically between 20 and 30 cm but often do not include data for Australian water bodies and/or small river sections. Our approach using pixel cloud data achieves an accuracy of ∼5 cm in measuring water heights over rivers as narrow as ∼40 m wide and reservoirs as small as ∼ 100×100 m, well below the mission requirements of 100 m river width and 250×250 m lake area.